2001
DOI: 10.1021/jm011015q
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Polycyclic Acridines. 8. Synthesis and Telomerase-Inhibitory Activity of Methylated Pentacyclic Acridinium Salts

Abstract: Two short routes to novel methylated pentacyclic quinoacridinium salts have been devised. New compounds display telomerase-inhibitory potency (<1 microM) in the TRAP assay. 3,11-Difluoro-6,8,13-trimethyl-8H-quino[4,3,2-kl]acridinium methosulfate (12d, RHPS4, NSC 714187) has a higher selectivity for triplex and quadruplex DNA structures than the 3,6,8,11,13-pentamethyl analogue (12c, RHPS3, NSC 714186) and a low overall growth-inhibitory activity in the NCI 60 cell panel (mean GI(50) 13.18 microM); in addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
116
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(122 citation statements)
references
References 32 publications
5
116
1
Order By: Relevance
“…The number of G4 ligands has grown rapidly over a few years: a range of molecules has been shown to inhibit telomerase through binding to its substrate [14,26,27,36,[44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59]. On the other hand, few natural products have been reported as G-quadruplex-mediated telomerase inhibitors, although one, telomestatin, is exceptionally potent with an IC50 of 5 nM against telomerase [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of G4 ligands has grown rapidly over a few years: a range of molecules has been shown to inhibit telomerase through binding to its substrate [14,26,27,36,[44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59]. On the other hand, few natural products have been reported as G-quadruplex-mediated telomerase inhibitors, although one, telomestatin, is exceptionally potent with an IC50 of 5 nM against telomerase [25].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, specific recognition of unusual DNA structures such as triplexes and quadruplexes by small molecules such as pyridoacridines should be possible. RHPS4 (center) [27,54,66,67]…”
Section: Introductionmentioning
confidence: 99%
“…The following drugs were used: clinical-grade irinotecan (CAMPTO, Pfizer, Borgo S Michele, LT, Italy), pentacyclic acridine RHPS4 (Heald et al, 2002), NU1025 used at a concentration of 200 mM (Santa Cruz Biotechnology, Santa Cruz, CA, USA) and orally bioavailable PARP inhibitor GPI 15427 used at a concentration of 2 mM (Eisai, Baltimore, MD, USA). Drugs were freshly prepared before each experiment.…”
Section: Drugsmentioning
confidence: 99%
“…In the acridine chromophore aniline substituent at 9 th position shows significant inhibitor activity for the Compound 6 (BRACO19) (IC 50 0.095 µM) and Compound 7 (IC 50 0.060 µM) [14]. The pentacyclic quinoa iridium salt RHPS4 (Compound 8) (IC 50 0.25 µM) shows good pharmaceutical properties and efficiently transported into tumor cells [15]. Other acridine compounds such as polycyclic acridines (Compound 9) (IC 50 0.37 µM) [16], quaternized quinoa [4, 3, 2-kl] acridinium salts (Compound 10) (IC 50 0.38 µM) [17], and 3, 6, 9-trisubstituted acridine derivatives (Compound 11) (IC 50 0.018 µM) have been reported [18] and showed best telomerase inhibitor activity.…”
Section: Acridine Derivativesmentioning
confidence: 99%
“…Wheelhouse et al [24] reported cationic porphyrins, and among them, they found one of the Compound 23 (TMPyP4- [5,[10][11][12][13][14][15]20-tetra-(-N-Methyl-4-pyridyl)] porphine) as it stabilizes and stacked with G-Quadruplex DNA and inhibits telomerase enzyme with an IC 50 value of 6.5±1.4 µM. Analogs of TMPyP4 (e.g., Compound 24 -IC 50 5 µM) have been reported and found as the positively charged substituent's on meso positions, and the size of substitution are important, and the face of porphyrins should be available for stacking [25].…”
Section: Porphyrine Derivativesmentioning
confidence: 99%